PENGARUH PENGGUNAAN VIDEO ANIMASI TERHADAP KETERAMPILAN MENULIS PESERTA DIDIK PADA MATERI TEKS EKSPLANASI DI KELAS III SDN KADUGEDE - Ayi Nurnanengsih; Riza Fatimah Zahrah; Deni Chandra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by the low writing of third-grade students on explanatory text material at SDN Kadugede. One effort that can be made to improve students’ writing skills is by using engangin and interactive learning media,namely animated videos. This study aimed to determine the effect of using animated videos on students writing skills in explanatory text material in the third grade of SDN Kadugede. This study employed a quantitative approach with an experiemental method. The research design used was a pretes-posttest design. The subjects of the study were third-grade students of SDN Kadugede. Data were collected through writing skill tests administered before and after the implementation of animated video-based learning. The collected data were analyzed using statistical tests to determine the effect og animated videos on students writing skills. The results of study showed that there was an improvement in students writing skills after participating in learning activites using animated videos. The average posttest score was higher than the average pretest score. Thefore, it can be concluded that the use of animated videos has a positive effect on students writing skills in explanatory text material in the third grade of SDN Kadugede.